Anaerobic microbial Fe(II) oxidation and Fe(III) reduction in coastal marine sediments controlled by organic carbon content. (27th June 2016) - Laufer, Katja; Byrne, James M.; Glombitza, Clemens; Schmidt, Caroline; Jørgensen, Bo Barker; Kappler, Andreas
Summary: Coastal marine sediments contain varying concentrations of iron, oxygen, nitrate and organic carbon. It is unknown how organic carbon content influences the activity of nitrate‐reducing and phototrophic Fe(II)‐oxidizers and microbial Fe‐redox cycling in such sediments. Therefore, microcosms were prepared with two coastal marine sediments (Kalø Vig and Norsminde Fjord at Aarhus Bay, Denmark) varying in TOC from 0.4 to 3.0 wt%. The microcosms were incubated under light/dark conditions with/without addition of nitrate and/or Fe(II). Although most probable number (MPN) counts of phototrophic Fe(II)‐oxidizers were five times lower in the low‐TOC sediment, phototrophic Fe(II) oxidation rates were higher compared with the high‐TOC sediment. Fe(III)‐amended microcosms showed that this lower net Fe(II) oxidation in the high‐TOC sediment is caused by concurrent bacterial Fe(III) reduction. In contrast, MPN counts of nitrate‐reducing Fe(II)‐oxidizers and net rates of nitrate‐reducing Fe(II) oxidation were comparable in low‐ and high‐TOC sediments. However, the ratio of nitratereduced :iron(II)oxidized was higher in the high‐TOC sediment, suggesting that a part of the nitrate was reduced by mixotrophic nitrate‐reducing Fe(II)‐oxidizers and chemoorganoheterotrophic nitrate‐reducers. Our results demonstrate that dynamic microbial Fe cycling occurs in these sediments and that the extent of Fe cycling is dependent on organic carbon content.